Discourse markers of enunciative responsibility in Portuguese stand-up comedy - Morozova, Milana A. (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
This contribution explores the role of discourse markers in signaling enun- ciative responsibility (ER) (i.e. a mechanism that allows evaluating the degree of authorship displayed in texts) in a particular genre – Portuguese stand-up comedy. The research is situated within Text Linguistics; specifically, on Textual Analysis of Discourses (Adam 2008). The main interest lies within the scope of markers of ER, which attribute different points of view (PoV) to various parts of texts and include three categories: marker-mediators (“de acordo com” according to, “segundo” conforming to, etc.), markers of reformulation (“isto é” that is, “em outras palavras” in other words, etc.), and markers of conversational structure (“bom” well, “você vê/tu vês” you see, “você sabe/tu sabes” you know, etc.). Applying both quantitative and qualitative methods to a collected corpus, not only are the frequency and the distribution of different categories of markers of ER analyzed, but the equivalence of the degree of responsibility in all the three categories is questioned. The results of the analysis show an uneven distribution among the three categories of discourse markers of ER: while the markers of conversational structure are highly present in the oral data, marker-mediators are almost absent. The paper then looks at the category of ER in terms of qualitative analysis, and verifies that for marker-mediators the responsibility is not assumed by the comedian, while in the case of the markers of reformulation there is a partial assumption of responsibility. As for the markers of conversational structure, although all the three categories are included in the group called “markers of ER”, conversational structure is less perceivable and would benefit from a recategorization or another theory to account for it.